2019
DOI: 10.1016/j.psychres.2018.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of interoception predict premonitory urges and tic severity in Tourette syndrome

Abstract: Dimensions of interoception predict premonitory urges and tic severity in Tourette syndrome.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 50 publications
3
41
1
Order By: Relevance
“…Despite the apparent straightforward relation between premonitory urges and tics (i.e., tics are the result of premonitory urges), the exact pathophysiological relevance of these phenomena remains unclear (37,38), and several models have been proposed to explain the presence of excessive bodily sensations (35,36,(39)(40)(41). According to one promising line of research, the capacity to perceive premonitory urges is related to the overall capacity to perceive interoceptive signals (41,42), possibly providing an explanatory framework to understand the associations of premonitory urges with other clinical symptoms, such as anxiety or obsessive-compulsive behaviors (25,(43)(44)(45)(46). Interestingly, patients with TS are less well able to perceive their own physiological interoceptive signals (41,42,47).…”
Section: The Sensory Manifestations Of Ts That Evoke the Concept Of Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the apparent straightforward relation between premonitory urges and tics (i.e., tics are the result of premonitory urges), the exact pathophysiological relevance of these phenomena remains unclear (37,38), and several models have been proposed to explain the presence of excessive bodily sensations (35,36,(39)(40)(41). According to one promising line of research, the capacity to perceive premonitory urges is related to the overall capacity to perceive interoceptive signals (41,42), possibly providing an explanatory framework to understand the associations of premonitory urges with other clinical symptoms, such as anxiety or obsessive-compulsive behaviors (25,(43)(44)(45)(46). Interestingly, patients with TS are less well able to perceive their own physiological interoceptive signals (41,42,47).…”
Section: The Sensory Manifestations Of Ts That Evoke the Concept Of Dmentioning
confidence: 99%
“…According to one promising line of research, the capacity to perceive premonitory urges is related to the overall capacity to perceive interoceptive signals (41,42), possibly providing an explanatory framework to understand the associations of premonitory urges with other clinical symptoms, such as anxiety or obsessive-compulsive behaviors (25,(43)(44)(45)(46). Interestingly, patients with TS are less well able to perceive their own physiological interoceptive signals (41,42,47).…”
Section: The Sensory Manifestations Of Ts That Evoke the Concept Of Dmentioning
confidence: 99%
“…This raises the possibility that insight abilities follow a 'U-shaped' curve, although in our present dataset, we were limited in our ability to explore this by the much smaller group of participants (n = 5) who showed low accuracy and high confidence, combined with the fact that the magnitude of their discrepancy is much smaller (0 to 0.3) than those showing the opposite (up to 0.7). www.nature.com/scientificreports www.nature.com/scientificreports/ We did not observe effects between decisions to act and trait-level awareness of interoceptive ability, measured using trait interoceptive prediction error (TIPE), which indexes discrepancy between an individual's objective (accuracy) and belief-based subjective (sensibility) dimensions of interoception 28,29 . State-based (e.g.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, in people with Tourette Syndrome, who experience uncomfortable bodily sensations preceding involuntary tics, sensitivity to bodily sensations predicts severity of their premonitory urges to move 29,58 . This is further evidence that interoceptive signals can cue motor behaviour, via signals to midline motor regions 12,59 .…”
Section: Discussionmentioning
confidence: 99%
“…Ganos et al 27 demonstrated that interoceptive perception is an important predictor of the severity of sensory phenomena measured by the Premonitory Urges for Tics Scale (PUTS) 28 in TS patients. Rae et al 29 demonstrated that the severity of sensory phenomena in their sample of TS patients correlated positively with interoceptive sensitivity, but not with interoceptive perception -which presented a significant positive correlation only with tics severity measured by the global severity scale (Yale Global Tic Severity Scale, YGTSS) 30 . Still, several functional neuroimaging studies show that areas involved in interoceptive processes activate just before the occurrence of tics; for example, conducted the first study to evaluate neurofunctional correlates of tics and reported that, during tic occurrence, there was significant hyperactivation as measured by positron emission tomography, insula, somatosensory cortex, and SMA.…”
Section: Rdoc Constructs and Ocd: Sensory Phenomena As An Examplementioning
confidence: 99%